Development and Role in Therapy of Canakinumab in Adult-Onset Still’s Disease - Galozzi, Paola; Baggio, Chiara; Bindoli, Sara; Oliviero, Francesca; Sfriso, Paolo (Frontiers in Pharmacology, 2018)
Adult-onset Still’s disease (AOSD) is a rare inflammatory disease of unknown aetiology typically characterized by episodes of spiking fever, evanescent rash, arthralgia, leukocytosis and hyperferritinemia. The pivotal role of interleukin (IL)-1 and other pro-inflammatory cytokines gives rise to the development of new targeted therapies. Currently, AOSD patients can benefit from efficient and well tolerated biologic agents, such as IL-1, IL-6 and tumour necrosis factor (TNF)-α antagonists. Canakinumab, a human monoclonal anti-IL-1β antibody, is indicated for the treatment of different autoinflammatory syndromes in adults, adolescents and children and it has recently been approved for AOSD treatment. In this article, we summarize the structural and biochemical data describing the molecular interactions between Canakinumab and its target antigen. Some special considerations of the pharmacological properties of Canakinumab are included. We also review the safety, efficacy and tolerability of this drug for the treatment of AOSD.